Case report: A novel PTCH1 frameshift mutation leading to nevoid basal cell carcinoma syndrome - Lang, Xiaoqing; Wang, Ting; Guo, Shuping; Dang, Yao; Zhang, Yingjie; Liu, Hongye; He, Hongxia; Li, Li; Yuan, Huajie; He, Ting; Wang, Qiong; Qin, Shiyu; et al. (Frontiers in Medicine, 2024)
A patient presenting with several basal cell carcinomas, pigmented nevi, and developmental defects was diagnosed with nevoid basal cell carcinoma syndrome. Gene panel sequencing and Sanger sequencing were used to identify a novel heterozygous frameshift mutation, c.1312dupA:p.Ser438Lysfs, in exon 9 of PTCH1. I-Tasser and PyMol analyses indicated that the mutated protein patched homolog 1（PTCH1） lacked 12 transmembrane domains and the intracellular and extracellular rings of ECD2 compared with the wild-type protein, resulting in a remarkably different structure from that of the wild-type protein. This case extends our knowledge of the mutation spectrum of NBCCS.